Cochlear, auditory brainstem responses in Type 1 diabetes: relationship with metabolic variables and diabetic complications. Issue 9 (29th December 2015) - Lasagni, A.; Giordano, P.; Lacilla, M.; Raviolo, A.; Trento, M.; Camussi, E.; Grassi, G.; Charrier, L.; Cavallo, F.; Albera, R.; Porta, M.; Zanone, M. M.
Abstract: Aims: Few studies have analysed the presence of hearing abnormalities in diabetes. We assessed the presence of subclinical auditory alterations and their possible association with early vascular and neurological dysfunction in young adults with Type 1 diabetes of long duration. Methods: Thirty‐one patients with Type 1 diabetes (mean age 33 ± 2.3 years, disease duration 25.7 ± 4.2 years) and 10 healthy controls underwent pure tone audiometry (PTA), distortion product otoacoustic emission (DPOAE) and auditory brainstem response (ABR) analyses. Associations with metabolic variables and chronic complications were explored. Results: Compared with healthy controls, patients with diabetes had significantly higher mean hearing thresholds, although still within the normoacusic range. DPOAE intensities at medium frequencies (2.8–4 kHz) were significantly lower in patients with diabetes. In ABR, in addition to waves I, III and V, we observed the appearance of a visible wave IV in patients with diabetes compared with controls (prevalence 61% vs. 10%, P < 0.05), and its appearance was related to a prolonged I–V interval (4.40 ± 0.62 ms vs. 4.19 ± 0.58 ms, P < 0.05). Diastolic blood pressure was higher in people with abnormal DPOAE ( P < 0.05), whereas systolic blood pressure correlated with wave V and interpeak I–V interval latencies. A trend towards an association between evidence of wave IV and the presence of somatic neuropathy or abnormal cardiovascular autonomic tests was observed. Conclusions: Young adults with long‐term Type 1 diabetes have subclinical abnormalities in qualitative auditory perception, despite normal hearing thresholds, which might reflect neuropathic and/or vascular alterations. What's new?: Auditory function involves the cochlea and neural transmission, making the ear a potential 'window' through which to evaluate microvascular and neurological abnormalities associated with chronic hyperglycaemia. We tested the presence of auditory alterations in young adults with long‐term Type 1 diabetes. We detected a qualitative auditory dysfunction, reflecting cochlear dysfunction. Otoacoustic emission alterations are associated with higher blood pressure, indicating a possible role for vascular mechanisms. A delay in acoustic nerve transmission and the presence of somatic or autonomic neuropathy are observed. In young adults with Type 1 diabetes, abnormalities of auditory perception might reflect neuropathic and/or vascular alterations.